2018
DOI: 10.1016/j.jpeds.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond race and ethnicity to understand the effect of inhaled nitric oxide on bronchopulmonary dysplasia prevention

Abstract: In their study, Blaisdell et al conclude that diuretics do not "substantially improve the respiratory status of the infant born extremely premature." 1 I disagree with this interpretation. The main outcome measure of the study was "change in the respiratory status," defined on the basis of 5 very broad categories ("deceased," "endotracheal tube," "continuous positive airway pressure or nasal cannula >2 liters per minute," "nasal cannula <2 LPM," and "no support"; their Table II) that are not sensitive enough t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A reduction in rate of this outcome was found in the African American population but not the white or Hispanic groups 196 . This observation may be regarded as hypothesis-generating and an appropriate basis for further prospective randomized controlled trials 197 .…”
Section: Short-term Managementmentioning
confidence: 94%
“…A reduction in rate of this outcome was found in the African American population but not the white or Hispanic groups 196 . This observation may be regarded as hypothesis-generating and an appropriate basis for further prospective randomized controlled trials 197 .…”
Section: Short-term Managementmentioning
confidence: 94%
“…Finally, definition of race was based on maternal self-identification. 45 Furthermore, iNO exposure duration may be brief in some of these neonates, and although propensity modeling was done in these neonates, all confounding factors may not have been adjusted. Also, because most grade III/IV IVHs occur during the first 3 days of life, especially in infants with HRF, the exposure to iNO and IVH could be incidental.…”
Section: Figurementioning
confidence: 99%
“…The impact of these variables on the observed treatment effect was not considered. Without a thorough understanding of the interplay of race/ethnicity and these other exposures, we risk therapeutic misuse of iNO in the preterm population [78]. Thus, while the findings of RiNOP are hypothesis-generating, further prospective, randomized clinical trials are necessary to evaluate the observed treatment effect [79].…”
Section: Is There a Race-specific Treatment Effect Of Ino In The Preterm Infant Population?mentioning
confidence: 99%